Identification of the epitopes on HCV core protein recognized by HLA-A2 restricted cytotoxic T lymphocytes - Zhou, Hong-Chao (World J Gastroenterol, 2001)
AIM: To identify hepatitis C virus (HCV) core protein epitopes recognized by HLA-A2 restricted cytotoxic T lymphocyte (CTL). METHODS: Utilizing the method of computer prediction followed by a 4 h (51)Cr release assay confirmation. RESULTS: The results showed that peripheral blood mononuclear cells (PBMC) obtained from two HLA-A2 positive donors who were infected with HCV could lyse autologous target cells labeled with peptide “ALAHGVRAL (core 150-158)”. The rates of specific lysis of the cells from the two donors were 37.5% and 15.8%, respectively. Blocking of the CTL response with anti-CD4 mAb caused no significant decrease of the specific lysis. But blocking of CTL response with anti-CD8 mAb could abolish the lysis. CONCLUSION: The peptide (core 150-158) is the candidate epitope recognized by HLA-A2 restricted CTL.